Restoring credibility in policy making in Ireland - John FitzGerald (The Economic and Social Research Institute (ESRI), 2011)
This paper first considers the origins of the Irish economic crisis. It discusses where the policy failures occurred, to what extent they were foreseeable, and how certain key financial institutions performed in the run up to the crisis. In the light of this analysis the paper then considers what institutional changes could feasibly be implemented which would strengthen policy making for the future.
Keywords: 330